2020
DOI: 10.12688/wellcomeopenres.16002.1
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 RNA detected in blood products from patients with COVID-19 is not associated with infectious virus

Abstract: Background: Laboratory diagnosis of SARS-CoV-2 infection (the cause of COVID-19) uses PCR to detect viral RNA (vRNA) in respiratory samples. SARS-CoV-2 RNA has also been detected in other sample types, but there is limited understanding of the clinical or laboratory significance of its detection in blood. Methods: We undertook a systematic literature review to assimilate the evidence for the frequency of vRNA in blood, and to identify associated clinical characteristics. We performed RT-PCR in serum samples fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 46 publications
6
73
0
2
Order By: Relevance
“…The search identified 2837 publications, and 21 studies involving 2182 patients were finally included 5,21‐40 (Figure 1). A retrospective study design was used in the majority of included studies (17/21).…”
Section: Resultsmentioning
confidence: 99%
“…The search identified 2837 publications, and 21 studies involving 2182 patients were finally included 5,21‐40 (Figure 1). A retrospective study design was used in the majority of included studies (17/21).…”
Section: Resultsmentioning
confidence: 99%
“…Arguably, the mere detection of viral RNA in the blood/serum does not reflect infectivity of a virus. Andersson et al (2020) found that all their reverse transcription-polymerase chain reaction (RT-PCR)-positive clinical samples show neither viral replication nor display any cytopathic effect after inoculation in cell culture [ 64 ]. More studies are warranted to resolve these uncertainties.…”
Section: Sars-cov-2 and Pregnancymentioning
confidence: 99%
“…In our proposed model, severe COVID-19 alveolitis is intimately associated with a lung vasculopathy, with extrapulmonary effects potentially stemming from the unique way in which the virus interferes with the physiology of the tricompartmental model. Generally, SARS-CoV-2 RNA is not detectable in the blood in milder infection, but can be detected in some severe cases [49][50][51][52] and correlates with interleukin-6 concentrations in critically ill patients. 53 Patients with detectable RNA in the blood were found to be older and to have more comorbidities, and were more likely to require ICU admission and mechanical ventilation.…”
Section: Other Aspects Of Pathology In the Vascular Compartmentmentioning
confidence: 99%